Oral supplementation with a prebiotic, mannan oligosaccharide, mitigates intestinal dysbiosis in young rats chronically exposed to passive smoking - Silva, Bruna Rafaela dos Santos; Gonçalves, Robson Diego Silva; Sasso, Vanessa Teixeira Paolino; Bremer-Neto, Hermann; Keller, Rogeria (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
In humans, passive smoking has been shown to alter the microbiota and increase the risk of infections by pathogens and/or opportunistic bacteria. The objective of this study was to evaluate the effect of MOS supplementation on the concentration of E. coli in the feces of passive smoking rats. Sixty young rats (23 days) were randomly allocated into four groups (n=15): supplemented or not with MOS in the diet; and chronically exposed or not to cigarette smoke. Exposure to cigarette smoke was performed twice a day for 180 days and fecal samples were collected four times (days 0, 60, 120, and 180). After fecal collection, bacterial populations were amplified by real-time PCR. Data means were analyzed using one-way ANOVA followed by Student-Newman-Keuls post-hoc analysis, considering 5% as the level of significance. The results revealed that MOS supplementation significantly (P<0.05) reduced the E. coli population resulting from chronic exposure to cigarette smoke. The mean results of the group of rats supplemented with MOS and exposed to cigarette smoke did not differ (P>0.05) from the groups not exposed to cigarette smoke and supplemented or not with MOS. The results allow us to conclude that MOS supplementation mitigates the chronic effect of cigarette smoke on the concentration of E. coli bacteria in young rats, as a preclinical model.